HUBUNGAN KOMPETENSI DAN MOTIVASI DENGAN KINERJA DINAS SOSIAL KABUPATEN WONOSOBO - Nilam Adini Rakhma; Susi Sulandari; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
In every organization qualified element is needed to maximize performance. The human resources that the organization has have a variety of characteristics, including job competence, motivation and performance. The role of human resource in the organization is important because this source will become the factor that drives the organization to achieve its intended purpose. This study was conducted to determine the relationship of competence and motivation with the performance of Wonosobo district’s social service. This study used quantitative research with technique of sampling all employees who are 18 respondents. The analysis used was Spearman rank correlation test. Findings from the study indicate that the hypothesis which stated that there is a positive correlation between the ability and motivation to the performance of Wonosobo District’s Social Service is significantly acceptable with correlation coefficient value of each relationship is; the relationship between the performance of Wonosobo District’s Social Service with competence, is 0609 and the relationship between Wonosobo District’s Social Service performance of Wonosobo District’s Social Service with work motivation, is 0662. The result of the study showed a positive and significant relationship between competence and motivation with performance of Wonosobo District’s Social Service. This means that by increasing the competence and organizational performance will increase with increasing the motivation to increase organizational performance .